A Model for Sleep Apnea Management in Underserved Patient Populations. (January 2022) - Henry, Olivia; Brito, Alexandra; Lloyd, Marguerite Cooper; Miller, Robert; Weaver, Eleanor; Upender, Raghu
Introduction: Obstructive sleep apnea (OSA) is a common condition in the United States that is strongly linked to metabolic disease, cardiovascular disease, and increased mortality. Uninsured populations experience sleep health disparities, including delayed recognition, diagnosis, and treatment of OSA due to barriers accessing and affording care. Partnerships between primary care clinics and sleep medicine specialists for sleep apnea management have the potential to increase screening, testing, and treatment among underserved populations. Here, we present an integrated and cost-effective model that is easier to navigate for patients while maintaining high quality care. Methods: We designed and implemented a specialty sleep clinic at Shade Tree Clinic, Vanderbilt's student-run, free primary care clinic. Patients with signs and symptoms of OSA were identified at primary care appointments and screened using the STOP-BANG questionnaire. Clinic visits took place over telehealth with a medical student and sleep specialist. Patients were diagnosed using a home sleep test, and if indicated, were prescribed and given a CPAP device for treatment. CPAP adherence was monitored using a cloud-based remote monitoring system. Results: From December 2020 through August 2021, we hosted 6 telehealth Sleep Clinics, seeing a total of 28 patients across these visits. We have received a total of 37 referrals and have coordinated sleep evaluations and diagnostic testing for 18 of these patients so far. Prior to initiation of the sleep clinic, there were 17 patients on our primary care panel at Shade Tree with a diagnosis of OSA. These patients were using donated equipment and many had been lost to follow-up or had broken parts. We were able to replace 10 of these patient's CPAP devices and plan to replace the remaining seven. Conclusions: We have created a model of integrated specialty care that is efficient and cost-effective. This paradigm can be replicated for the many specialties that are typically overlooked and undertreated when working with uninsured patients. As awareness of this sleep medicine program becomes more widespread at Shade Tree Clinic, we anticipate reaching more primary care patients with signs and symptoms of sleep apnea through student education, cost-effective diagnostics, and partnership with sleep specialists.